Comparative toxicity of urban wastewater and rainfall overflow in caged freshwater mussel Elliptio complanata - André, C.; Duy, S. V.; Sauvé, S.; Gagné, F. (Frontiers in Physiology, 2023)
Municipal effluents are well-recognized as disrupting sexual differentiation and reproduction in mussels. However, the contribution to this problem made by rainfall combined with sewer overflow (increased by rain due to climate change) is not well understood. The purpose of this study was to compare the neuroendocrine effects of municipal discharge and rainfall overflow on caged endemic mussel Elliptio complanata. To this end, mussels were experimentally caged and placed for 3 months at a municipal effluent dispersion plume site and at overflow sites. Data revealed that downstream surface water contained some pharmaceuticals (caffeine and carbamazepine) and accumulated significant levels of heterotrophic bacteria, but these effects were not observed at the overflow sites. The principal effects observed at the downstream site were increased soft tissue mass (and gonad index), inflammation, and Vtg proteins in male mussels as determined by a novel immunostaining methodology. The rainfall overflow sites had no effects on these markers, but were specifically associated with reduced Vtg proteins in females, dopamine (Dop), gonad lipids, and DNA strand breaks, with increased metallothioneins. In conclusion, the observed feminizing effects of municipal effluent were not additionally observed in mussels caged at rainfall overflow sites, although the latter exhibited a different pattern of toxicity.